Development of power recovery circuit for bio-implantable stimulator - Alghrairi, Mokhalad Khaleel; Sulaiman, Nasri; Mohd Sidek, Roslina; Mutashar, Saad (Universiti Putra Malaysia Press, 2017)
This paper presents a modified design of low power recovery circuit in micro-system implanted device to stimulate the human nerve and muscle. The amplitude shift keying ASK was used to modulate data by using operating frequency 6.78MHz ISM industrial scientific medical band to be less invasive to tissue. The proposed system consists of an external part which has ASK modulator and class-E power amplifier with 94.5% efficiency. The internal part has half wave rectifier and voltage regulator to generate very stable 1.8VDC using 0.35um CMOS technology. The Orcad pspice 16.6 and MULTISIM 11 software were used to simulate the design of power recovery and class-E power amplifier respectively. The regulated voltage utilised to power the sub-electronic device implanted inside human body with very stable voltage even change implanted load resistance. The proposed system has 12.5%modulation index and low power consumption.